47.6k views
2 votes
What is the first step to solve -2x+5x=9​

2 Answers

1 vote

Answer:

add the x's

You have to combine them

you have to subtract the -2x to the 5x

User FacesOfMu
by
5.4k points
2 votes

Answer:

Explanation:

Hello,

You need to group the terms in x


-2 * x + * x = (-2+5) * x = 3 x

And then, you can divide by 3 to find the solution


-2x+5x=3x=9<=>x=9/3=3

Hope this helps

User FarligOpptreden
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.